FAKTOR PENDORONG DAN PENARIK WISATAWAN BACKPACKER MANCANEGARA BERWISATA KE BALI - Manik, Gayatri; Suwena, I Ketut; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata); Vol 4 No 2 (2016): Jurnal IPTA (December 2016)DO - 10.24843/IPTA.2016.v04.i02.p04)
Trend backpackers is growing in various areas, including in Bali. Backpackers have been identified as having “a preference for budget accommodation, independently organized travel and emphasis on meeting other travellers, longer rather than brief holidays. The purpose of this research are to anlyses the push and pull factors that motivate the foreign backpacker tourists traveled to Bali. Sample on this research is 200 respondents of backpackers and using purposive sampling technique. Offline questionnaires are used for data collecting and the analysis technique is based on factor analysis. The results of research shows that the push factors backpackers traveled to Bali are (1) facilitation of social interaction, (2) self-identity, (3) relaxation, (4) prestige, (5) adventure (6) novelty. The push factor that dominantly is facilitation of social interaction. The pull factors are (1) cultural/historical, (2) affordable price, (3) variety seeking, (4) tourism facilities, (5) safety and clean, (6) environment. The pull factor that dominantly is Cultural / Historical.
Keywords: Factor Analysis, Push & Pull Factor, Backpacker Tourist